Dzieciństwo w mieście na ziemiach polskich w XVI–XVIII wieku – możliwości źródłowe i perspektywy badawcze - Żołądź-Strzelczyk, Dorota (Biuletyn Historii Wychowania, 2011)
The issues of a child and childhood in the Polish territories have been neglected by historians for a long time. One of the reasons for this situation was the lack of appropriate sources for such studies. On one hand, the sources for analysing the history of childhood are relatively scarce; on the other hand, the sources that exist do not often provide much information. Thus, in order to reconstruct the functioning of a child in those times a researcher must confront numerous sources concerning various aspects of town life. The sources include the legal sources (statutes, constitutions) as well as court, iconographic, school, personal/private, statistical, archeological and material sources. Their diversity and informative value depends on the size and wealth of a particular town. Bigger and more affluent cities produced more sources but they also did more for children, especially those who found themselves in a difficult situation – abandoned, orphaned or harmed.